Improving Reading Comprehension of the First Year Students Through Directed Reading Activity (DRA) Strategy in Narrative Text - Alfarisi, Muhammad Fadel; Aruan, Rumiri Rotua; Syarfi, M. (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study examined whether Directed Reading Activity (DRA) strategy could improve students’ reading comprehension in narrative text and to know the factors that influence reading comprehension in class X students of SMAN 10 Pekanbaru. This research used classroom action research design with quantitative and qualitative approach. The way to select the sample was by asking the teacher which class had the lowest English score and the total sample was 35 students. Data collected using pre-test, cycle I, and cycle II. The results revealed that the average mean in the pre-test was 47 (poor), in cycle I was 70 (good), and cycle II was 85 (excellent). Based on the study’s results, it can be concluded that by using Directed Reading Activity (DRA) strategy, students’ comprehension in narrative text has improved.